(untitled) (Polish Yearbook of International Law, 2016)
This article examines the process of the judicial Europeanization of the Polish Constitution. In Poland the judicial method of Europeanizing the Constitution is currently the primary way of adjusting constitutional norms to requirements resulting from EU law. The phenomenon of re-interpretation of constitutional provisions in light of the new and changing realities is a characteristic feature of contemporary constitutionalism. It has been a long time since most national constitutions have undergone significant textual changes. In Poland, the scope of judicial Europeanization of the Constitution is connected, to a great extent, with the inflexible procedure required for constitutional amendments. In this situation, these so-called “silent changes” of constitutional norms are the easiest and fastest way of reacting to requirements stemming from Poland’s EU membership. In the Polish case not only have the norms regarding the political system of the state changed, but also constitutional standards relating to the protection of fundamental rights and freedoms have undergone the process of the Europeanization. To some extent, these changes relate to procedural norms as well.